Human iPSCs stretch to improve tissue engineered vascular grafts - Abutaleb, Nadia (Cell Stem Cell, 2020)
Human induced pluripotent stem cells (hiPSCs) provide a potentially unlimited cell source for producing autologous tissue-engineered vascular grafts (TEVGs), which currently suffer from low mechanical strength. Luo et al. (2020) describe optimized culture media and a mechanical stretching regiment to produce hiPSC-derived TVEGs with mechanical behavior similar to natural vessels.